(3cJGH aj JGQjN GdESdGes
(3ChdgG (B:s
(3GdcdGe Ydi NdGaI GHhHcQ GdUOjb s
(3BNQgG (B:s
(3BNQg MhGOK SfI (B805(3g` s
(3bO OS HYVge ai Chd GdcJGH aPcQ HNW MOjK Cfg GdLRA GdKGfi ef JGQjN GdESdGe ddMGaX GdPgHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B243 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs